Comparative Analysis of the Mechanical Strength of Bamboo Fiber-Reinforced Polyester Composites with Random and Unidirectional Fiber Orientations - Hen lie Yu; Jiangfu Wu; Yantiex Gao; Zanfin Lu; Wenzhan Hu (Gio Vani Publisher, 2026)
This study investigates the tensile properties of polyester-based composites reinforced with bamboo fibers, with particular emphasis on the effect of fiber orientation. Composite materials are formed by combining a matrix and a reinforcing phase to achieve improved mechanical performance. In this research, unsaturated polyester resin was used as the matrix, while bamboo fibers served as natural reinforcement due to their availability, low cost, and favorable mechanical characteristics. The specimens were fabricated using the hand lay-up method with two different fiber orientations: random and longitudinal (unidirectional). Tensile testing was conducted to evaluate the mechanical behavior of the composites, including ultimate tensile strength, yield strength, and strain. The results show that the addition of bamboo fibers enhances the tensile properties of the polyester resin compared to the neat resin, which exhibited brittle behavior and limited elongation. Composites with random fiber orientation demonstrated higher average tensile strength but also showed greater variability, indicating less uniform stress distribution. In contrast, composites with longitudinal fiber orientation exhibited more consistent mechanical properties due to better alignment of fibers with the direction of applied load, resulting in more efficient stress transfer. Overall, the findings highlight the importance of fiber orientation in determining the mechanical performance of natural fiber-reinforced composites. Longitudinal fiber alignment is recommended for applications requiring stable and reliable mechanical behavior, while random orientation may be considered where higher peak strength is desired under certain conditions.